Contribuição ao estudo da reação á tricofitina nas dermatofitoses - Vilani-Moreno, Fátima Regina; Arruda, Maria Sueli Parreira de [UNESP] (Instituto de Medicina Tropical, 1992)
Os autores investigaram a competência imunológica específica de 31 indivíduos portadores de dermatofitose, utilizando o antígeno tricofitina. Destes, 54,8% mostraram-se reatores à fase tardia dessa prova (48 h) nas seguintes proporções: tinea inguinale, 75%; tinea pedis, 61,5%; tinea unguium, 50% e tinea corporis, 20%. 62,5% dos casos apresentaram positividade à fase imediata (30 m) da reação. A associação entre essas reações revelou que, embora a maioria dos pacientes com reação imediata positiva apresentasse negatividade à reação tardia, 20,8% apresentaram positividade para as duas fases da reação. Dos pacientes não reatores à fase tardia, oito foram submetidos a outros testes cutâneos: PPD, estreptoquinase, candidina, vacínia e DNCB, verificando-se imunidade celular conservada em 75% dos casos. Estes resultados sugerem que, quando da utilização dessa prova na avaliação imunológica de pacientes com dermatofitose, deve-se considerar o estado imune geral do paciente, a presença de hipersensibilidade imediata e a localização da infecção.

The authors investigated the specific immunological competence of 31 patients with dermatophytosis using tricophytin antigen. Among them, 54.8% showed reaction to the delay phase (48 h) in the following proportions: tinea inguinale, 75%; tinea pedis, 61.5%; tinea unguium, 50% and tinea corporis, 20%. Other 62.5% showed positive result to the early phase (30 m). The association between these reactions revealed that, although the majority of cases with early positive reaction showed negativity to the delayed reaction, 20.8% presented positivity to both phases of the reaction. Out of the non-reactive patients to the delayed phase, 8 were submitted to the other cutaneous tests such as PPD, streptokinase, candidin, vaccinia and DNCB and showed preserved cellular immunity in 75%. These results suggest that, while using this reaction for immunological evaluation of patients with dermatophytosis, one should consider the overall immune status of the patient, the presence of early hypersensibility and the localization of the infection.
Contribution to the study of the tricophytin reaction in dermatophytosis
Keywords: Dermatofitoses; Tricofitina